Mengungkap Kebenaran Pelanggaran HAM Masa Lalu di Era Transisi Demokrasi - Suparman Marzuki (Unisia, 2005)
The problem of state responsibility toward gross violation of human rights that con ducted by past regime denotes and becomes a crucial and complex problem Including the gross violation of human rights that happening in Indonesia. In term of this, for instances the cases of Tanjung Priok, Komando Jihad, Aceh, Talang Sari Lampung and so on. Because of the fall of New Order Regime, pro democracy powers as like South Africa, East Europe, The Latin America and Asia countries force to settle tha cases of human rights as prerequisite of democracy consolidation. According to author of the article that the responsibility of gross violation of human rights by past regime denotes an agenda for each transitional government because there are rights to know the truth, rights of justice, and rights to human dignity. The task of the regime is preparing the mechanism how to responsible for old regime.